Analisis Dampak Harga Gabah Terhadap Kesejahteraan Petani Padi Sawah di Desa Buttu Sawe Kecamatan Duampanua Kabupaten Pinrang - Rahman Rahman; Andi Nuddin; Andi Erna Sriwahyuningsih (Jurnal Agribis, 2023)
Buttu Sawe Village is one of the villages in Duampanua District, Pinrang Regency, where most of the area is agricultural land. The people in this village carry out agricultural business because from a geographical point of view the area still has a lot of agricultural land. The average ownership of agricultural land by rice farmers in Buttu Sawe Village is less than "partial" or agricultural land with an area of ​​approximately 2,000 m². Lowland rice farming in Buttu Sawe Village is the main sector that is the backbone of people's lives. If the rice crop is disturbed, it is certain that the food security of the community will be disturbed and the level of welfare of farmers will also be disturbed. Welfare of rice farmers can be seen from the ability of farmers to meet the basic needs of their lives and families, such as clothing, food, shelter, health and education. The welfare indicators include population, health and nutrition, education, employment, household consumption and housing. The aims of this study were: 1) To describe the level of welfare of lowland rice farmers in Buttu Sawe Village, Duampanua District, Pinrang Regency and 2) To describe the effect of grain prices on the welfare of lowland rice farmers in Buttu Sawe Village, Duampanua District, Pinrang Regency. This research uses descriptive quantitative research methods. The research sample is 29 respondents who are rice farmers in Buttu Sawe Village. The instrument used in this study was a research questionnaire consisting of several questions regarding the variables studied. The data analysis technique used is descriptive statistical analysis and simple regression analysis with the help of the SPSS 16 program. From the results obtained: 1) The welfare level of lowland rice farmers in Buttu Sawe Village, Duampanua District, Pinrang Regency is 100% or all respondents are included as rice farmers. rice fields in the category of prosperous households, and 2) The price of grain has a significant effect on the welfare of rice farmers in Buttu Sawe Village, Duampanua District, Pinrang Regency.